(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
The purpose of this research is to investigate the relationship between work discipline and organizational performance, with a specific focus on the moderating role of organizational culture within Pakistan’s textile industry. The study aims to understand how work discipline and organizational culture impact the performance of textile firms in this context. Data was analyzed using SPSS, employing descriptive statistics as well as factor and regression analyses. A questionnaire utilizing a Likert scale was used to gather data from the Punjab textile sector, with purposive sampling applied. While the research initially targeted 230 participants, 203 responses were ultimately analyzed. The results reveal a strong and positive correlation between work discipline, organizational culture, and organizational performance. Specifically, work discipline is positively associated with improved organizational performance. Furthermore, organizational culture is shown to positively influence performance, highlighting its role in moderating the relationship between work discipline and performance. These findings underscore the significant impact of both work discipline and organizational culture on enhancing organizational outcomes. In conclusion, organizational culture plays a critical moderating role, amplifying the positive effects of work discipline on organizational performance. Future research should explore additional factors that may influence employee performance, including managerial support, work environment, job satisfaction, and individual personality traits. It is also recommended that future studies be guided by current literature and consider aspects of organizational commitment